KEBERHASILAN IMPLEMENTASI PADA STRATEGI PENGEMBANGAN KOMODITI NENAS DENGAN PENDEKATAN ONE VILLAGE ONE PRODUCT (OVOP) DI KABUPATEN SIAK - Jhordy Hadith Ramadhan; Hasim As'ari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
An effort that can be done to reduce disputes between development activities in urban and rural is to develop people' economic potential based on local potential.  In this case the Siak Regency' government policy is to use an One Village One Product (OVOP) approach which is a one-product one-village program that leads to the concept of developing the agricultural subsector by exploring the potential of resources that can be developed through leading commodities in each region.  Pineapple commodity in Sungai Apit Subdistrict is one of the leading commodity development in Siak Regency, with abundant production, local government and communities have not been optimal in its management.  So the results achieved are not optimal.  This research method used qualitative methods with a case study approach.  Data collection is done by interview, observation and documentation.  Based on data collected then by assessing the reality in society,  the results indicate that the first implementation of the development of pineapple commodity in Siak Regency has not been running optimally.  The two factors that hinder the development of pineapple commodities in Siak Regency are coordination that is not going well, resource conditions are still weak and ineffective marketing and promotion and the location of the Siak Regency is far from trade flow. Keywords: Implementation, Strategy, One Village One Product (OVOP)